Item quality analysis using the Rasch model to measure critical thinking ability in the material of the human digestive system of Biology subject in high school - Prasetya, Wanda Agus; Pratama, Anggi Tias (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
This study aims to determine the quality of the Biology instrument items on the digestive system material with the Rasch model for analyzing critical thinking skills. The research employed a quantitative descriptive method involving 63 students of senior high schools in Yogyakarta. The data were collected using a critical thinking skills description test and processed using the Rasch model with the Winstep 5.0.3.4 program. The study shows that the overall validity is acceptable. The item validity did not require improvement in items 14, 3, 8, 13, 12, 1, 4, 10, 6, 2, 7, 11, 15, and 9, and required improvement or replaced of item 5 because it did not fit. The analysis result using Cronbach's alpha shows that the overall reliability is very good, and the item reliability is good. Rating scale analysis using partial credit ratings and probability curves shows that respondents need help understanding the five-point Likert scale. The analysis of the item difficulty based on Logit and Wright maps shows that the most difficult item to work on is item 14. Items with moderate categories are items 13, 12, 1, 4, 10, 6, 2, 5, and 7. Items easy to work on are items 11, 15, and 9. The bias results show item 14 gender-biased. The results of the interaction between the item and the person through the ICC plot image show that all items are on the curve of the outfit confidence space and follow the Rasch modeling.